Analisis Kesulitan Siswa Dalam Memahami Konsep Materi Momentum Dan Impuls Di SMA Muhammadiyah Kota Serang - Paramitha, Devitriana Putri; Oktarisa, Yuvita; Antarnusa, Ganesha (Peneliti.net, 2024)
This research was conducted to find out the difficulties experienced by class XII students of SMA Muhammadiyah Serang City in understanding the concepts of momentum and impulse. This research uses a qualitative method with a population of class XII who have studied momentum and impulse material, then the sample is all students of class From the results of written tests and interview tests, it was found that the learning difficulties and lack of understanding of concepts experienced by students came from not paying attention when the material was given, as well as misperceptions when working on questions, and a lack of use of the correct formula equation for each quantity being calculated or searching for.